Assessment of Scrape-Off Layer and divertor plasma conditions in JT-60SA with tungsten wall and nitrogen injection. (March 2021) - Rubino, G.; Calabrò, G.; Wischmeier, M.
Abstract: The possibility to safely operate tokamaks strongly depends on the capability to protect the divertor targets from excessive power load and erosion. Here, we will present a study of the JT-60SA Scenario 3 with a W wall to identify possible criticality in the transition from C to W wall. The assessment of the SOL and divertor plasma conditions is made with the SOLPS-ITER code suite. The simulations results show that safe operations are mainly limited by T e . In addition, the analysis of the balance equations highlights the importance of the impurity injection. It represents the main mechanism to drive the decrease in power load onto the outer target ( P O T ) by impurity radiation and to achieve detachment via the collisions between D + ions and D 2 molecules. Highlights: First work with SOLPS-ITER on JT-60SA equipped with a fully metal wall (W). Assessment of the safe conditions in terms of main plasma contamination. Evaluation of physical mechanism able to trigger detachment and to decrease power load onto outer divertor plates. Assessment of possible operational windows.